2017
DOI: 10.1093/bib/bbx084
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamical incompleteness of the Protein Data Bank

Abstract: Major scientific challenges that are beyond the capability of individuals need to be addressed by multi-disciplinary and multi-institutional consortia. Examples of these endeavours include the Human Genome Project, and more recently, the Structural Genomics (SG) initiative. The SG initiative pursues the expansion of structural coverage to include at least one structural representative for each protein family to derive the remaining structures using homology modelling. However, biological function is inherently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Protein movements were classified using different criteria (for example ( Qi et al., 2005 ; Amemiya et al., 2012 ) and following those criteria it was found that the dynamical behaviour is mostly not conserved during evolution ( Marino-Buslje et al., 2019 ).…”
Section: And Yet It Moves ( E Pur Si Muove )mentioning
confidence: 99%
“…Protein movements were classified using different criteria (for example ( Qi et al., 2005 ; Amemiya et al., 2012 ) and following those criteria it was found that the dynamical behaviour is mostly not conserved during evolution ( Marino-Buslje et al., 2019 ).…”
Section: And Yet It Moves ( E Pur Si Muove )mentioning
confidence: 99%
“…The existence of conformational ensembles is known since the crystallization of hemoglobin with its two conformational states T and R (deoxy and oxygenated forms) in the early 1960. The growth of Protein Data Bank (PDB) redundancy, refinement and development of techniques such as NMR, SAXS and single molecule spectroscopy over the last years have allowed the experimental characterization of a large number of protein ensembles 2,3 . Structural differences between conformers could result from the relative movements of large domains as rigid bodies 4 , secondary and tertiary element rearrangements 5 , and loop movements 6 .…”
Section: Introductionmentioning
confidence: 99%
“…43 More recently, we found that the dynamical behavior in a given family could change with minor sequence variations making difficult to predict CD by homology. 63 Distributions in Figure 1 show that CD could be as large as the MSD, but it is also evident that most of the proteins in our dataset have modest to low CD, meaning that they could function with very low or absent backbone movements. 43,64,65 Several studies drew attention to the importance of CD in TBM methods, 18,19,27 but the consideration of CD in the study of structure-sequence relationships, as an essential ingredient in TBM methods, was often considered a source of bias or "noise."…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, we have recently shown that the distribution of CD in a large dataset of proteins, with experimentally determined CD (approximately 5000 proteins), results in three main groups of proteins with different structure‐function relationships . More recently, we found that the dynamical behavior in a given family could change with minor sequence variations making difficult to predict CD by homology …”
Section: Discussionmentioning
confidence: 99%